Adopsi Fashion Halal Pada Wanita Sosialita : Teori Planned Behaviour - Muhammad Ardi; Srigandawati Srigandawati; Mutiyah Mahdin; Haslindah Haslindah (Jurnal Ilmiah Al-Tsarwah, 2024)
This study analyzes the influence of religiosity, attitudes and subjective norms on Halal Fashion Adoption through the mediation of intention. This research is a correlational survey research with the support of questionnaire data from 200 respondents from Socialite Females in Bone. Data analysis and hypothesis testing were carried out through structural equation modeling. This test was carried out through three testing stages, namely: EFA test which was analyzed using the SPSS software application, CFA test and SEM (Structural Equation Modeling) test using the LISREL version 8.70 statistical application. The results show that socialite females in Bone districs rejects the Planned Behavior Theory and must be supported by other theories. The use of halal fashion is only influenced by Subjective Norms and intentions are influenced by the behavior of adopting halal fashion. However, there is also the potential for religiosity and attitudes to influence this behavior. It was found that socialite females in using halal fashion only followed what was trending.